Effects Of Acrylonitrile-Butadiene Latex Powder On The Impact And Thermal Properties Of Poly(Lactic Acid) - Kamal, Nurul Farihah (Universiti Sains Malaysia, 2017)
Polylactic acid (PLA)/acrylonitrile butadiene rubber (NBR) latex blends were prepared using internal mixer followed by compression molding. The blending ratio of PLA/NBR are 95:5, 90:10, 85:15, 80:20, 75:25 and 70:30. The objective of this research is to study the effect of NBR latex powder on the impact and thermal properties of PLA. The NBR latex powder was prepared by NBR latex compounding followed by drying and grinding process. The mechanical and morphological properties of PLA/NBR blends were characterized by Charpy impact test and Scanning Electron Microscopy (SEM). The thermal properties of PLA/NBR blends were determined using Thermogravimetric Analyzer (TGA) and Differential Scanning Calorimeter (DSC). Fourier Transform Infrared (FTIR) Spectroscopy was used to determine the intermolecular interactions of the PLA/NBR blends. It was found that the impact strength of PLA was increased by addition of NBR latex powder. This is due to the elastomeric behaviour of NBR latex powder itself. The glass transition temperature of PLA was reduced by the incorporation of NBR latex powder, which indicates the increased flexibility of PLA/NBR blends. Nevertheless, from the TGA measurement, the results showed that the addition of NBR latex powder reduced the thermal stability of PLA.